Interpretative Phenomenological Analysis: A means of exploring aspiration and resilience amongst Widening Participation students. (31st May 2017) - Gauntlett, Lizzie; Bickle, Ed; Thomas, Gail; Collins, Bethan; Heaslip, Vanessa; Eccles, Sue
As the Office for Fair Access and the Higher Education Funding Council for England priorities now extend across widened access to success, both the aspirations of young people from widening participation (WP) backgrounds and their existing or developing resilience as students are of concern to Higher Education institutions. In this paper, these positive psychology concepts of aspiration and resilience are used in two different studies each seeking to move away from the prevalent discourse of deficit. This paper thus offers the joint perspective of two researchers exploring the phenomena of a) aspiration in students from low participation neighbourhoods and b) resilience in students from low-income backgrounds. Interpretative Phenomenological Analysis (IPA) is utilised by both to offer a credible, insightful research approach which may enable educators, researchers and policy-makers to appreciate the nature and significance of WP students' experiences in a previously unseen way, thus enabling effective interventions and methods of support. Through in-depth exploration of the cognitions and emotions of young people from WP backgrounds, the researchers discuss how listening to individual stories can provide rich data that may enhance future support for students. Important methodological challenges and the implications of applying IPA to both studies are debated; including use of language to convey meaning, the role of researcher reflexivity and the difficulties in achieving a truly interpretative account of the phenomenon. Whilst often a challenging methodology, IPA can provide rich, contextualised accounts which contribute to the limited extant qualitative literature on WP student aspiration and resilience.